Developing Data Centralization Interactive Media for 7th Grade Students’ Statistical Literacy Using SAC Application - Sari, Laela; Prasetyo, Puguh Wahyu (Universitas Ahmad Dahlan, 2025)
The aim of this research is to develop interactive media that utilizes the Smart Apps Creator (SAC) application with a focus on statistical literacy, especially on data centralization material for grade 7 students. The development of this media follows the steps in the ADDIE model, namely analysis, design, development, implementation, and evaluation. This research involved 25 7th-grade students from SMP Muhammadiyah 3 Depok Sleman as research subjects. The instruments used in this research include interviews, validation questionnaires from material and media experts, and student response questionnaires. Based on research findings, interactive media developed with the Smart Apps Creator (SAC) application is proven to be valid and practical. The results of the material expert assessment were 80% which met the valid category. While the media expert assessment was 81.48% met the very valid category. The practicality criteria were obtained from the results of student responses with a percentage of 79.44% which also fell into the practical category indicating that the media is suitable for use in teaching. Thus, interactive media based on SAC can be an effective alternative to improve student understanding and motivation when studying data centralization material.